Knowledge and Cases Used for the Diagnosis and Treatment of Foot-Mouth-Cattle Diseases in Jimma Zone of Ethiopia - Gojeh, Lawrence Abraham; Alemu, Mesfin; Neda, Seifu (International Journal For Research In Advanced Computer Science And Engineering, 2021)
Foot-Mouth-Cattle Disease is one of the most serious livestock diseases that the virus is highly contagious, which affects cloven-hoofed animals (those with divided hoofs), including cattle, buffalo, camels, sheep, goats, deer and pigs. It deeply affects the productivity, losses of livestock, causing hardships for farmers and ranchers, disrupting regional and international trade in animals. The objective of this study assessed the knowledge and cases of foot-mouth-cattle diseases used by domain experts for the diagnosis and treatment of the disease at Seka Chokorsa and Shebe Sombo Weredas in the Jimma zone of Ethiopia. Acquiring of such previous knowledge and solved cases will go a long way to helping cattle rural farmers tackle or overcome the prevailing problems associated with the disease in the domain area through developing technological systems for the rural cattle farmers to diagnose and treat the disease. A cross-sectional survey research method was used to gather preliminary data through questionnaire, interview and observation schedules from domain experts that included Veterinary doctors, Development agents and Model rural cattle farmers. The data collected supported the researchers make inferences about the relationships of previous knowledge and cases diagnosed and treated of the disease in the study area. The study found that the domain experts had previous knowledge and cases of the viruses that transmits the foot-mouth-cattle diseases. The two categories of domain experts (Veterinary doctors and Development agents), identified serotypes viruses ‘A’ (25%); ‘C’ (12.5%) and ‘SAT-1, SAT-2 and SAT-3’ (37.5%) with ‘SAT-1, SAT-2 and SAT-3’ as the most prevalent. However, model rural farmers indicated the most affecting serotype virus as ‘A’ (50%) and 25% for ‘SAT-1, SAT-2 and SAT-3’ in the domain area. This finding should form a base for the development of a knowledge base system for the diagnosis and treatment of foot-mouth-cattle disease for the rural cattle farmers at Seka Chokorsa and Shebe Sombo Weredas in the Jimma zone of Ethiopia.